Plasma and erythrocyte uptake of omega-3 fatty acids from an intravenous fish oil based lipid emulsion in patients with advanced oesophagogastric cancer. Issue 3 (June 2017) - Eltweri, A.M.; Thomas, A.L.; Fisk, H.L.; Arshad, A.; Calder, P.C.; Dennison, A.R.; Bowrey, D.J.
Summary: Background: It has been demonstrated that short term intravenous (IV) administration of omega-3 polyunsaturated fatty acids (PUFAs) is more effective than oral supplementation at promoting incorporation of the bioactive omega-3 PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) into plasma, blood cells and tissues. The effect of repeated short term IV infusion of omega-3 PUFAs was investigated in patients with advanced oesophagogastric cancer during palliative chemotherapy. Methods: Patients with advanced oesophagogastric cancer (n = 21) were recruited into a phase II pilot clinical trial. All patients were scheduled for an intravenous infusion of Omegaven ® (fish oil supplement containing EPA and DHA) at a rate of 2 ml/kg body weight for 4 h once a week for up to six months. Blood samples were collected to assess omega-3 PUFA uptake into plasma non-esterified fatty acids (NEFAs) and phosphatidylcholine (PC) and into red blood cell (RBC) membranes. Fatty acid profiles were analysed by gas chromatography. Results: Twenty patients received at least one Omegaven ® treatment and were included in the analysis. Each infusion of omega-3 PUFAs resulted in increased EPA and DHA in plasma NEFAs, but there was little effect on PUFAs within plasma PC during the infusions. However, with repeated weekly infusion of omega-3 PUFAs, the EPA content of plasma PC and of RBC membranes increased. Conclusion: Repeated weekly omega-3 PUFA infusion is effective in enriching plasma PC and RBC membranes in EPA in patients with advanced oesophagogastric cancer receiving palliative chemotherapy. Trial Registration : Clinical Trials.GovNCT01870791 .